Theoretical analysis of limitations to maximum sprinting speed imposed by muscle mechanical properties - Miller, R. H.; Umberger, B. R.; Caldwell, G. E. (34th annual meeting of the American Society of Biomechanics at Brown University Providence, Rhode Island on August 18 - 21, 2010, 2010)
Maximum running speed is an important parameter during many athletic competitions. Running speed is determined by stride length and stride frequency. While both increase directly with speed, maximum sprinting speed is reached when stride frequency can no longer be increased. The force-velocity relation of skeletal muscle has thus been implicated as a critical limiting factor in speed achievement. Other muscular properties such as forcelength and activation dynamics have been shown to influence the control of walking and jumping. At maximal speed, lower extremity muscles undergo substantial length and activation changes; these properties may also influence running speed. Thus, our purpose was to evaluate the effects of removing various muscle mechanical properties on the achievement of maximum sprinting speed. Since it is impossible to remove muscle mechanical properties in vivo, a computer simulation approach was used to systematically test the limiting effects of specific properties on sprint performance. University of Massachusetts, Amherst, MA, USA web: http://www.umass.edu/biomechanics